Determination of Optimal Process Parameters In The Process Of Making Ceramics To Maximize Flexural Strength Using the Taguchi Method (Case Study at the Kasongan Ceramics UKM Center, Bantul, DIY) - Sutrisno Sutrisno Sutrisno; Dyah Rachmawati Lucitasari (OPSI, 2021)
Kasongan Ceramic UKM Center is an association of UKM which makes goods made from clay. Kasongan Ceramic UKM Center, located in Bantul Regency, DIY. The problem that is often experienced by Kasongan Ceramics Center is that products that are often cracked, warped, and easily brittle. The total production of Kasongan UKM Center from September 2019 to February 2020 was 32,256 units, with the number of defective products amounting to 3,873 or 12% of the total production. Based on the studies that have been done, it can be concluded that the defects of cracks, curling, and brittleness that occur are one of them caused by the less than optimal flexural strength of the ceramic products produced. To maximize the flexural strength of the ceramic products produced, the optimal ceramic manufacturing process parameters will be determined using the Taguchi method. To maximize the flexural strength in the process of making ceramics using the Taguchi method, it is necessary to do an experimental design. The first thing to do is to determine the controlled factors and levels in the ceramic manufacturing process that affect the flexural strength. After that determine a suitable orthogonal array and perform experiments based on the specified orthogonal array. The experimental results will be tested for its flexural strength in the laboratory. The resulting flexural strength data will be processed to determine the optimal ceramic manufacturing process parameters that maximize the bending strength of ceramics. Based on the data processing carried out, it is found that the optimal ceramic-making process parameters at the Kasongan Ceramics UKM Center that maximize flexural strength are the composition of 3 parts Godean clay, 3 parts Kasongan clay composition, 1 part sand composition, and burning using an open tub.